2019
DOI: 10.33112/nm.14.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Ósýnileiki barna sem leita alþjóðlegrar verndar á Íslandi í fylgd foreldra

Abstract: Flóttamannastofnun Sameinuðu þjóðanna (UNHCR) áætlar að á árinu 2017 hafi um 68,5 milljónir einstaklinga verið á flótta, þar af sé rúmlega helmingur börn (UNHCR, 2018). Umsækjandi um alþjóðlega vernd er hver sá sem hefur flúið heimaríki sitt og sótt um að fá viðurkennda stöðu flóttamanns og dvalarleyfi hjá stjórnvöldum annars ríkis (Rauði krossinn, e.d.). Mikil aukning hefur orðið á slíkum umsóknum á Íslandi undanfarið og er nokkur fjöldi barnafjölskyldna þar á meðal. Árið 2015 voru 79 börn á meðal umsækjenda … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Mental health problems have been found amongst migrant youth in Iceland [21], although research on mental health issues concerning children and youth who seek asylum in Iceland is absent. Nonetheless, a qualitative study reported that accompanied asylum-seeking children and youth in Iceland experienced invisibility during the asylum process and were not encouraged to express their opinions on matters of importance to them, such as their mental health and adaptation in Iceland [22].…”
Section: Introductionmentioning
confidence: 99%
“…Mental health problems have been found amongst migrant youth in Iceland [21], although research on mental health issues concerning children and youth who seek asylum in Iceland is absent. Nonetheless, a qualitative study reported that accompanied asylum-seeking children and youth in Iceland experienced invisibility during the asylum process and were not encouraged to express their opinions on matters of importance to them, such as their mental health and adaptation in Iceland [22].…”
Section: Introductionmentioning
confidence: 99%